Impact of Information Space on Economic Security in the Region - Andrei Gennadievich Svetlakov; Irina Mikhaylovna Glotina (Экономика региона, 2018)
The article deals with the relevant issue of the influence of information space on the current state of economic security of Russian regions. In the modern society, the information space is an objectively existing phenomenon, which performs a number of constructive and destructive functions and has a direct impact on the economic security of regions. The research of Russian and foreign scientists in the field of information theory, philosophy, mathematics, economics have become the theoretical and methodological basis of the paper. Transition to the information society has changed the status of information resources. The analysis of the statistical data of authoritative Russian and foreign sources has allowed us to reveal the main tendencies of modern society. Information processes have the most significant impact on such areas as health and safety, education, science, culture, socio-political sphere, as well as the quality of life. However, threats to economic security are under transformation. Therefore, there is a need for changes in the assessment of the economic security of regions. We proposed a technique for the evaluation of economic security based on the comprehensive assessment of several groups of indicators. The number of groups and a set of estimated indicators can be defined by experts. The results of the proposed method are demonstrated on the example of eight Federal Districts of Russia. The authors used official statistics, since they covered different spheres of citizens throughout the whole state territory. The assessment includes 32 indicators distributed into nine groups: economy, food, information resources, etc. Calculations have revealed the regions with lower security level — Siberian and North-Caucasian Federal Districts. The proposed methodological approach and quantitative estimates can be used to predict and improve economic security management in regions.